Using Animated Video Based on Scientific Approach to Improve Students Higher Order Thinking Skill - Helmia Tasti Adri; Yudianto SA; Annisa Mawardini; Afridha Sesrita (Indonesian Journal of Social Research (IJSR), 2020)
This research is motivated by the desire to make a change to conventional and monotonous ways of learning by providing variations in science learning for students, where so far learning has been fixated on old media that are not relevant to the demands of innovation in education namely skill-based learning in the 21st century and the industrial revolution 4.0. The purpose of this study was to determine the effect of the use of video animation based on a scientific approach to the high-level thinking skills of students. The sample in this study were students majoring in Primary teacher education programs in science education, which were determined by cluster random sampling techniques. The study used an experimental methodology with a pretest-posttest control design. (3) T-test results from the results of the analysis of high-level thinking skills scores of students showed a significance value of 0.002 <0.05, proving that the final ability of the experimental class group was significantly higher than the control class. This indicates that the use of scientific animated video approaches influences students' high-level thinking skills.